Evolvement rule and hydrodynamic effect of fluid field around fish-like model from starting to cruising. Issue 1 (1st January 2020) - Gang, Xue; Yanjun, Liu; Weiwei, Si; Yifan, Xue; Fengxiang, Guo; Zhitong, Li
Abstract : Underwater vehicles are widely used in underwater detection, and bionic design, e.g. imitating fish, is an important way to improve their hydrodynamic performance. Most research is on the mechanical structure and kinematics of fish-like models, while evolvement rules and hydrodynamic effects of fluid field around fish have not been studied adequately. In this paper, a kinematic model to simulate the swimming motion of fish is established according to the actual movement of tuna, and the model is optimized to achieve convenient adjustment in the initial oscillating position and maximum oscillating amplitude. A numerical simulation model is established and the boundary condition is verified by experiments with a physical fish-like prototype and a set of force measuring devices. The evolvement rule of the fluid field around the fish-like model from starting to cruising is determined and the hydrodynamic effect is analyzed. The issue of the effect of fluid fields with various averaged fish-like model densities in the buoyancy regulating process is discussed. Finally, a novel way to calculate the Strouhal number is proposed. The results show that the averaged drag force coefficient decreases as the fish-like model speeds up, because the water pressure near the fish head strengthens to generate a larger resistance force and the vortex in the wake field disperses to produce a less positive effect. The viewpoint that the superposition of vortices will benefit the fish-like model instead of weakening the positive effect is confirmed. The width value of the reversed Kármán vortex street can be connected with the Strouhal number, and the Strouhal number can be calculated by the evolvement rule of the fluid field. This research will contribute to bionic autonomous underwater vehicle design.